Revealing differences in the chemical form of zinc in brain tissue using K-edge X-ray absorption near-edge structure spectroscopy - Hollings, Ashley; Lam, Virginie; Takechi, Ryu; Mamo, John; Reinhardt, J.; De Jonge, M.D.; Kappen, P.; Hackett, Mark (ROYAL SOC CHEMISTRY, 2020)
Zinc is a prominent trace metal required for normal memory function. Memory loss and cognitive decline during natural ageing and neurodegenerative disease have been associated with altered brain-Zn homeostasis. Yet, the exact chemical pathways through which Zn influences memory function during health, natural ageing, or neurodegenerative disease remain unknown. The gap in the literature may in part be due to the difficulty to simultaneously image, and therefore, study the different chemical forms of Zn within the brain (or biological samples in general). To this extent, we have begun developing and optimising protocols that incorporate X-ray absorption near-edge structure (XANES) spectroscopic analysis of tissue at the Zn K-edge as an analytical tool to study Zn speciation in the brain. XANES is ideally suited for this task as all chemical forms of Zn are detected, the technique requires minimal sample preparation that may otherwise redistribute or alter the chemical form of Zn, and the Zn K-edge has known sensitivity to coordination geometry and ligand type. Herein, we report our initial results where we fit K-edge spectra collected from micro-dissected flash-frozen brain tissue, to a spectral library prepared from standard solutions, to demonstrate differences in the chemical form of Zn that exist between two brain regions, the hippocampus and cerebellum. Lastly, we have used an X-ray microprobe to demonstrate differences in Zn speciation within sub-regions of thin air-dried sections of the murine hippocampus; but, the corresponding results highlight that the chemical form of Zn is easily perturbed by sample preparation such as tissue sectioning or air-drying, which must be a critical consideration for future work.